2006
DOI: 10.1681/asn.2006091009
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Role for Relaxin as a Renal Vasodilator

Abstract: S triking renal and cardiovascular adaptations occur early in human pregnancy, including increases in intravascular volume and cardiac output. Despite these adaptations, and because of a marked reduction in systemic vascular resistance, blood pressure (BP) falls (1,2). One of the earliest and most dramatic changes is the increase in renal plasma flow (RPF) and GFR due to renal vasodilation (3). Animal studies indicate a role for the ovarian hormone relaxin (RLX) (4,5), and the report by Smith et al. (6) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
3
2
0
Order By: Relevance
“…Finally, relaxin also plays an important role in vascular and renal adaptations during gestation 34). The reno-vasodilatory properties of relaxin have been reported in preclinical models 35 , 36 consistent with those described in healthy subjects or heart failure patients 20 . The effect of SA10SC-RLX on renal blood flow in rats is in line with the improvement of renal function by relaxin in patients with heart failure 37 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Finally, relaxin also plays an important role in vascular and renal adaptations during gestation 34). The reno-vasodilatory properties of relaxin have been reported in preclinical models 35 , 36 consistent with those described in healthy subjects or heart failure patients 20 . The effect of SA10SC-RLX on renal blood flow in rats is in line with the improvement of renal function by relaxin in patients with heart failure 37 .…”
Section: Discussionsupporting
confidence: 77%
“…In healthy subjects and heart failure patients, relaxin increases renal plasma flow (RPF) 20 . Thus, we compared the effect of SA10SC-RLX and relaxin on renal blood flow (RBF) in rats to generate translational data.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, relaxin also plays an important role in vascular and renal adaptations during gestation (Mc Guane et al 2009). Reno-vasodilatory properties of relaxin have been reported in preclinical models (Danielson et al 1999, Deng et al 2018) consistent with those described in healthy subjects or heart failure patients (Sasser et al 2006). The effect of SA10SC-RLX on renal blood ow in rats is in line with the improvement of renal function by relaxin in patients with heart failure (Unemori et al 2017).…”
Section: Sa10sc-rlx Effect In a Translational Model Of Renal Blood Owsupporting
confidence: 69%
“…In healthy subjects and heart failure patients, relaxin increases renal plasma ow (RPF) (Sasser et al 2006). Thus, we compared the effect of SA10SC-RLX and relaxin on renal blood ow (RBF) in rats to generate translational data.…”
Section: Sa10sc-rlx Effect In a Translational Model Of Renal Blood Owmentioning
confidence: 99%
“…Relaxin plays important roles in vascular and renal adaptations during gestation. In healthy subjects and heart failure patients, relaxin increases renal plasma flow (RPF) (Smith et al, 2006) and eGFR (Dahlke et al, 2015) consistent with its renovasodilatory properties reported in preclinical models (Sasser et al, 2006). Deterioration of kidney function is an important prognostic factor for worsening heart failure.…”
Section: R2r01 Effect In a Translational Model Of Rbfsupporting
confidence: 66%